Efficacy of Aloe vera, Ananas comosus, and Sansevieria masoniana Cream on the Skin Wound Infected with MRSA - Yos Adi Prakoso; Chylen Setiyo Rini; Roeswandono Wirjaatmadja (Advances in Pharmacological Sciences)
The tropical area has a lot of herbal medicines such as Aloe vera (AV), Ananas comosus (AC), and Sansevieria masoniana (SM). All the three have a unique potential effect as an antibacterial and wound-healing promoter. The aim of this study is to explore the role of AV, AC, and SM on the skin wound infected with methicillin-resistant Staphylococcus aureus (MRSA). Forty-five adult female Sprague Dawley rats weighing 250–300 grams were divided into 5 groups. All the groups were exposed to two round full-thickness punch biopsy and infected with MRSA. The group C was the control group/untreated; group BC was treated with base cream/without extract; group AV was treated with 75% AV cream; group AC was treated with 75% AC cream, and group SM was treated with 75% SM cream. The wounds were observed on days 5, 10, and 15. The healing of skin wounds was measured by a percentage of closure, skin tensile strength, and histopathology. The result showed that AV, AC, and SM have a similar potential effect on healing in the wound that was infected with MRSA compared to the groups C and BC (P<0.05). It shows that all the three herbal formulations can be used as the alternative therapy to the wound infected with MRSA.